A homozygous donor splice-site mutation in the meiotic gene MSH4 causes primary ovarian insufficiency (2017)
Premature ovarian insufficiency (POI) is a frequent pathology that affects women under 40 years of age, characterized by an early cessation of menses and high FSH levels. Despite recent progresses in molecular diagnosis, the etiology of POI remains idiopathic in most cases. Whole-exome sequencing of members of a Colombian family affected by POI allowed us to identify a novel homozygous donor splice-site mutation in the meiotic gene MSH4 (MutS Homolog 4). The variant followed a strict mendelian segregation within the family and was absent in a cohort of 135 women over 50 years of age without history of infertility, from the same geographical region as the affected family. Exon trapping experiments showed that the splice-site mutation induced skipping of exon 17. At the protein level, the mutation p.Ile743_Lys785del is predicted to lead to the ablation of the highly conserved Walker B motif of the ATP-binding domain, thus inactivating MSH4. Our study describes the first MSH4 mutation associated with POI and increases the number of meiotic/DNA repair genes formally implicated as being responsible for this condition. © The Author 2017. Published by Oxford University Press. All rights reserved.